Factors that contribute to participation of youth in politics: a case study of UiTM Kedah’s student / Mohd Ikhwan Faiz Rodzi and Lutfi Shahir Muhammed Shariff - Faiz Rodzi, Mohd Ikhwan; Muhammed Shariff, Lutfi Shahir (2013)
Youth political participation can be determined when youth make an action which indicate that there participate in politics. The study examines the factors that contribute to youth political participation in Malaysia. A systematic sampling technique has been used to distribute the questionnaire to the respondents. The sample size of the study as according to the Krecjie and Morgan table is 234 respondents. The factors that contribute to youth political participation such as bandwagon factor, knowledge, and attitude had been explored. Results and findings of the research are based on the analysis done by using the descriptive frequency, Pearson Correlation ad Multiple Regression Analysis. Basically the findings of the research questions and objectives as well as the hypothesis have answered the research conducted by the researchers.